Blockchain in an Internet-of-Things Network Based on User Participation - Ljungblad, Robert (Luleå tekniska universitet, Datavetenskap, 2019)
The internet-of-things is the relatively new and rapidly growing concept of connecting everyday devices to the internet. Every day more and more devices are added to the internet-of-things and it is not showing any signs of slowing down. In addition, advancements in new technologies such as blockchains, artificial intelligence, virtual reality and machine learning are made practically every day. However, there are still much to learn about these technologies. This thesis explores the possibilities of blockchain technology by applying it to an internet-of-things network based on user participation. More specifically, it is applied to a use case derived from Luleå Kommun’s wishes to easier keep track of how full the city’s trash cans are. The goal of the thesis is to learn more about how blockchains can help an internet-of-things network as well as what issues can arise. The method takes an exploratory approach to the problem by partaking in a workshop with Luleå Kommun and by performing a literature study. It also takes a qualitative approach by creating a proof-of-concept solution to experience the technology firsthand. The final proof-of-concept as well as issues that arose during the project are analysed with the help of information gathered and experience gained throughout the project. It is concluded that blockchain technology can help communication in an internet-of-things network based on user participation. However, there is still a lot more to learn and uncover in future research. Internet-of-things är ett relativt nytt men snabbt växande koncept som handlar om att koppla upp vardagliga saker till internet. Varje dag kopplas mer och mer enheter upp och det visar inga tecken på att sakta ner. Det görs även framsteg inom andra nya teknologier som blockkedjor, artificiell intelligens, virtuell verklighet och maskininlärning i stort sett varje dag. Dock finns det fortfarande mycket att lära sig om dessa teknologier. Denna rapport utforskar blockkedjeteknologins möjligheter genom att applicera det på ett ...